1980
DOI: 10.1111/j.1365-2133.1980.tb07242.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrolatum: interference with the oxidation of arachidonic acid

Abstract: Microsomal preparations from petrolatum-treated wound skin contained significantly less arachidonic acid-dependent oxidative capacity when compared to activities in untreated wounded skin (t = 6.06, P < 0.001). Microsomes from both untreated and petrolatum-treated wounded skin produced similar quantities of PGE2 and PGF2 alpha; however, microsomal lipoxygenase activity in petrolatum-treated wounded skin was depressed when compared to that in untreated wounded skin. Microsomal preparations from normal pig skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A clear inhibitory effect of petrolatum on Th2 inflammatory responses was not observed by Czarnowicki et al; however, a reduction in inflammatory cell infiltrates was observed in petrolatum treated skin (54). Petrolatum has also been found to inhibit the synthesis of prostaglandins in the skin (56). Prostaglandins are important mediators of tissue inflammation in patients with AD.…”
Section: Artificial Restoration Of the Skin Barriermentioning
confidence: 90%
“…A clear inhibitory effect of petrolatum on Th2 inflammatory responses was not observed by Czarnowicki et al; however, a reduction in inflammatory cell infiltrates was observed in petrolatum treated skin (54). Petrolatum has also been found to inhibit the synthesis of prostaglandins in the skin (56). Prostaglandins are important mediators of tissue inflammation in patients with AD.…”
Section: Artificial Restoration Of the Skin Barriermentioning
confidence: 90%
“…LC have been observed in apposition to mononuclear inflammatory cells after merely occluding the skin with test patches of the Finn chamber type (12). On the other hand, Pennyes et al (13) have observed the inhibition of prostaglandin synthesis following application of petrolatum to skin wounds, suggesting that petrolatum may not be as neutral as previously believed.…”
Section: Discussusionmentioning
confidence: 93%
“…It is possible that apparently bland emollients have pharmacological properties—for example, studies in mice have demonstrated that the “placebo” effect of topical applications such as white soft paraffin or cetomacrogol cream results in part from antimitotic activity 22. In addition, some bland preparations have an anticyclo-oxygenase effect on the microsomal fraction of skin homogenates23 and this could account for many of the anti-inflammatory effects of these materials. Certain emollients, such as white soft paraffin, have been shown to have vasoconstrictor activity in the skin (to a lesser degree than topical corticosteroids) as well as a skin thinning effect (also to a lesser degree than topical corticosteroids) 24…”
Section: Discussionmentioning
confidence: 99%